Leaf Essential Oil Compositions and Enantiomeric Distributions of Monoterpenoids in Pinus Species: Pinus albicaulis, Pinus flexilis, Pinus lambertiana, Pinus monticola, and Pinus sabiniana - Alicia Moore; Elizabeth Ankney; Kathy Swor; Ambika Poudel; Prabodh Satyal; William N. Setzer (Molecules)
Members of the Pinus genus are well known for their medicinal properties, which can be attributed to their essential oils. In this work, we have examined the leaf essential oils of five understudied Pinus species collected from various locations in western North America. The essential oils were obtained by hydrodistillation and analyzed by gas chromatographic methods, including enantioselective gas chromatography. Pinus albicaulis was dominated by (+)-δ-3-carene; Pinus flexilis was dominated by α-pinene (mostly (+)-α-pinene) and (−)-β-pinene; Pinus lambertiana was dominated by (−)-β-pinene; Pinus monticola was dominated by (−)-β-pinene, (+)-δ-3-carene, and (−)-α-pinene; and Pinus sabiniana was rich in (−)-α-pinene and limonene. While this work adds to our knowledge of Pinus essential oils, additional research is needed to more fully appreciate the geographic and altitudinal variations in the volatile compositions of these Pinus species.